BIOREMEDIATION OF PALM OIL MILL EFLUENT BY USING Spirogyra Sp - Baihaqi, Baihaqi; Rahman, Mujibul; Ibrahim, Ibrahim (Universitas Almuslim, 2017)
One type of algae that potentially reduces palm oil mill effluent is Spirogyra sp. Spirogyra sp. Has a wide distribution on the coast of Indonesia and is still underutilized by pond farmers. This study aims to test the efficiency of Spirogyra as a bioremediation agent of palm oil liquid waste and to examine the effect of palm oil liquid waste on the growth of Spirogyra. This research was conducted from March to July 2017. The research design consisted of five treatments, namely treatment A control (0 mL.L-1), B treatment (25 mL.L-1), C treatment (50 mL.L-1) ), Treatment D (75 mL.L-1) and E treatment (100 mL.L-1). Observation parameters include absolute growth, relative growth rate, doubling time and water quality values (pH, temperature, salinity, dissolved oxygen and COD). The stastistic analysis used in this study uses one way ANOVA. The obvious different criteria used in this study was at a 95% confidence level (p <0.05). The results showed that Spirogyra was able to grow well on maintenance media containing oil palm liquid waste with concentration 25 mL.L-1 (treatment B). This can be seen from the absolute growth rate and the relative growth rate better than the treatment of C, D and E. Keywords: Palm Oil Mill Effluent, Spirogyra, Relative Growth Rate, COD